Effectiveness of The Padang Pariaman Disaster Emergency Preparedness Program (Papa Sadar Bana) Call Center 112 in Disaster Management in Padang Pariaman Regency - Alhadi, Zikri; Mandaita, Fathiaty; Yusran, Rahmadani (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study discusses the importance of the role of Information Technology in dealing with disaster problems in the Padang Pariaman Regency. Public service innovation by the government that utilizes Information Technology, namely E-Government, Program (Papa Sadar Bana) Call Center 112, is expected to help the community in disasters. This study uses the Theory of Effectiveness by Primanda (2017), namely with indicators of Program Target Accuracy, Program Socialization, Program Objectives, and Monitoring to measure the effectiveness of a program. This study aims to describe and understand the program effectiveness (papa conscious call center 112) in Disaster Management in Padang Pariaman Regency. The method used in this research is qualitative research with descriptive methods—data collection techniques in this study by interview, observation, and documentation. Furthermore, the informants in this study were the Head of BPBD of Padang Pariaman Regency, secretary, Call Center Staff 112, PUSDALOPS, TRC TEAM, Head of Sub-Division for Reconstruction & Rehabilitation and the Community.